Niños autónomos e independientes en Educación Inicial. - Sailema Bustos, Alexandra Del Carmen (2018)
The research "Autonomous and independent children of Initial Education" takes place in the Belisario Quevedo Educational Unit of Pujilí Canton, Cotopaxi Province, the study lies in the strategies to stimulate the acquisition of the skills of autonomy and independence in the infants of early education II. The research objectives are based on developing abilities in| self-sufficient and self-reliant children in the initial education through the bibliographic review. The methodology used in the research project has a qualitative and quantitative approach, a bibliographic and field design that uses the techniques of the interview, the survey and the observation for the data abstraction allowed to reach an exploratory level of the study, clarifying the main theoretical foundations of the self-sufficient children in the early education. It is important that both caregivers and educators are aware of the benefits of promoting autonomy and independence in children from early childhood, the contribution of research was theoretical because it supports the importance of autonomy and independence in child development. The beneficiaries of the research were the children, teachers and parents of the early education level II of Belisario Quevedo Educational Unit.